The Application of Good Agricultural Practices of White Pepper and Factors Affecting Farmer Participation - Rostiar Sitorus; Harianto Harianto; Suharno Suharno; Yusman Syaukat (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2020)
The productivity of white pepper plants and the low quality of yields are the main problems that should be corrected in the management of smallholder plantations in the Bangka Belitung Islands Province. This study aims to determine the factors affecting farmer participation in implementing GAP, as well as how the GAP was implemented. The study was conducted in 3 districts namely West Bangka, Central Bangka, and South Bangka as a center of white pepper production. The respondents consisting of 142 farmers who applied GAP and 82 non-GAP farmers. By using the logit model, it is found that older farmers, more educated, have more family members, have larger planting areas and farmers who are more active in participating in GAP socialization will have more chances of deciding to implement GAP. The implementation of white pepper GAP for each component, on average ranged from 67 to 95 percent.